UPAYA MENINGKATKAN AKTIVITAS BELAJAR SISWA MELALUI KOMBINASI MODEL PEMBELAJARAN KOOPERATIFTHINK-PAIR-SHARE DENGAN COURSE REVIEW HORAY - Layaliyana, Aifatun; Santoso, Sigit; Octoria, Dini (FKIP Universitas Sebelas Maret, 2016)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â The objective of this research is to improve the learning activities of the students in Grade XI IIS 3 of State Senior Secondary School 1 of Pelangi* in Academic Year 2015/2016 through the combination between the cooperative learning model of the think-pair-share type and the course review horay learning model.This research used the classroom action research with two cycles. Each cycle consisted of four phases, namelyplanning, implementation, observation and interpretation, and analysis and reflection. Its subjects were the students as many as 32 in Grade XI IIS 3 of State Senior Secondary School 1 of Pelangi*. The sources of the data were a teacher and students. The data were collected through observation, in-depth interview, and documentation. The observation was aimed to observe the improvement of the studentsâ learning activities, the interview was aimed to investigate the studentsâ response to the actions executed, and the documentation was aimed to collect the supporting data. The data were validated by using the data and method triangulations and analyzed by using the descriptive comparative technique of analysis.The results of research show that the combination the cooperative learning model of the think-pair-share type and the course review horay learning model can improve the studentsâ learning activities from Pre-cycle through Cycle II. In Pre-cycle the studentsâ learning activities were not optimal. The percentage of the students who were active in the learning activities was only 45.63%. Following the treatment, it became 69.38% in Cycle I and 83.75 in Cycle II. The stipulated indicator of performance for the studentsâ activeness in the learning activities was 80%.Thus, the combination the cooperative learning model of the think-pair-share type and the course review horay learning model can improve the learning activities of the students in Grade XI IIS 3 of State Senior Secondary School 1 of Pelangi* in 2015/2016.Keywords: Think-pair-share type, course review horay, learning activitiesÂ ABSTRAKTujuan penelitian ini adalah untuk meningkatkan aktivitas belajar siswa pada kelas XI IIS 3 SMA Negeri 1 Pelangi*Tahun 2015/2016 melalui kombinasi model pembelajaran kooperatif tipe think-pair-share dengan course review horay.Penelitian Tindakan Kelas ini dilaksanakan dalam dua siklus, dengan prosedur penelitian untuk masig-masing siklus meliputi empat tahap, yaituperencanaan tindakan, pelaksanaan tindakan, observasi dan interprestasi, dan analisis dan refleksi.Subjek penelitian ini adalah siswa kelas XI IIS 3 SMA Negeri 1 Pelangi* yang berjumlah 32 siswa.Sumber data berasal dari guru dan siswa.Teknik pengumpulan data adalah dengan observasi, wawancara, dan dokumentasi.Observasi untuk mengamati peningkatan aktivitas belajar siswa, wawancara untuk mengetahui respon terhadap tindakan yang dilakukan, dokumentasi digunakan untuk mengumpulkan data pendukung.Teknik validitas data menggunakanÂ menggunakan teknik trangulasi data dan triangulasi metode. Teknik analisis data menggunakan teknik analisis deskriptif komparatif.Hasil penelitian ini menunjukkan bahwa melalui kombinasi model pembelajaran kooperatif tipe think-pair-share dengan course review horay dapat meningkatkan aktivitas belajar siswa dari pratindakan, siklus I, dan siklus II. Pada pratindakan aktivitas belajar siswa belum optimal, hanya 45,63% siswa yang aktif. Penelitian ini menetapkan indikator kinerja sebesar 80%. Pada siklus I diperoleh presentase aktivitas belajar siswa meningkat sebesar 69,38% dan pada siklus II meningkat lagi menjadi sebesar 83,75%.Simpulan penelitian ini adalah melalui kombinasi model pembelajaran tipe kooperatif think-pair-share dengan course review horay dapat meningkatkan aktivitas belajar siswa pada kelas XI IIS 3 SMA Negeri 1 Pelangi* tahun 2015/2016.Â Kata Kunci: Model think-pair-share, course review horay, aktivitas belajar*) SMA Pelangi merupakan nama samaran